Pelatihan Manajemen Usaha Bagi Pengurus Dan Karyawan BMT Amanah Madinah Ngeni Waru Sidoarjo - Abdul Wahab (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Baitul Mal Wattamwil (BMT) as a microfinance institution, has experienced many obstacles in its business management. This training focuses on business management with the hope of increasing theoretical and practical understanding for employees and management. The methods used are lectures, questions and answers, and simulations, by first carrying out pre-training preparations and preparing all the necessities in their implementation. The results of the training showed that participants were enthusiastic to take part in the activity by providing suggestions for continuing activities on another day with a longer training time, as well as continuing training such as providing human resource management and service marketing techniques.